Grupos reflexivos para homens autores de violência doméstica: percepções das (os) profissionais da Central Integrada de Alternativas Penais - CIAP/SE - Mariano, Elissandra Barboza Santos (2025)
Gender inequalities are historically permeated by power relations and male domination over women, manifesting themselves in both public and private spaces and being reproduced by institutional practices. Within this context, this dissertation aims to analyze the perceptions of professionals working at the Integrated Center for Penal Alternatives (CIAP) regarding Reflective Groups for Male Perpetrators of Violence (GRHAV), considering the impact of these practices on combating violence against women. GRHAV emerged in Brazil in the 1990’s and gained greater visibility after the enactment of the Maria da Penha Law (LMP) in 2006, which, while not mandating their implementation, recognizes their importance as a protective measure. In Sergipe, the first experience with reflective groups was recorded in 2012, in the municipality of Lagarto. This qualitative, exploratory, case-study research is grounded in feminist epistemology, allowing for a broader understanding of the social inequalities and oppressions generated by the patriarchal, racist, and classist system, of which domestic violence is one of the most perverse expressions. The research universe encompasses professionals who work with GRHAV in the state of Sergipe. The sample consisted of two social workers, two psychologists, and one education professional affiliated with CIAP (Institutionalized Family and Adolescent Psychiatric Association). Content analysis was used for data analysis. As of June 2024, there were 14 reflective groups operating in the state. From its inauguration in 2020 to June 2024, CIAP served 687 (100%) men referred by the justice system. Among these, a representative sample of 169 subjects (24.5%) revealed the following predominant profile: Black men, aged between 30 and 59, low-income, single, and with incomplete elementary education. We concluded that the facilitators interviewed perceive the groups as important spaces that contribute to behavioral change, as participants come to understand that violence is not a natural act, but a social construct, which contributes to acknowledging their own actions and holding them accountable. The work developed by GRHAV is understood as a complementary strategy to legal measures, contributing to reducing the recurrence of violence against women. Although the groups represent powerful spaces for symbolic displacement, they still face limitations due to the complexity of the social, structural, and cultural relations that generate violence. The process of deconstructing hegemonic patterns of masculinity proves complex, highlighting the need for reflective groups to be linked to broader, intersectoral public policies.